169k views
4 votes
H (t) = -10t + 6

h ( ? ) = -44

I'm looking for the T that goes in the parenthesis

This is from Algebra 1 - Khan Academy, Unit Functions

User Terma
by
4.6k points

2 Answers

3 votes

Answer:

h(5)

Explanation:

Equate - 10t + 6 and - 44 and solve for t

- 10t + 6 = - 44 ( subtract 6 from both sides )

- 10t = - 50 ( divide both sides by - 10 )

t = 5 , that is

h(5) = - 44

User Nahuel Fouilleul
by
4.7k points
5 votes

Answer:


{ \tt{h(t) = - 10t + 6}} \\ - 44 = - 10t + 6 \\ - 10t = - 50 \\ t = 5

User Ola Herrdahl
by
4.6k points